Synthesis of new imidazothiazole derivatives and investigation of their anti-inflammatory and analgesic activities - Can, Oksan Soyer; Unlu, Serdar; Ocak, Hale; Coldur, Elif Cisem; Sipahi, Hande; Eran, Belkis Bilgin (SPRINGER, 2022)
In this study, new carboxamides derived from the imidazo[2,1-b]thiazole skeleton which are carrying the biologically active benzoxazole group and are terminated with polar group such as chloro/bromo/cyano as well as imidazothiazole-based methyl carboxylate derivative were synthesized in order to investigate anti-inflammatory and analgesic activities. The new molecules were characterized by FT-IR, H-1-NMR, C-13-NMR and ESI-MS spectrometry. New chloro-terminated imidazothiazole-based carboxamide (7a) and imidazothiazole-based methyl carboxylate derivative (8) showed, respectively, 75.88% and 77.05% cell viability on RAW 264.7 cell line at dose of 1.5 mu M and 50 mu M whereas trifluoroacetylamino-substituted thiazole carboxylate (1), trifluoroacetylamino-substituted thiazole carboxamides (2) and amino-substituted thiazole carboxamides (3) exhibited non-cytotoxicity by the cell viability value which is higher than 80% at dose of 100 mu M except for their brominated derivatives 2b and 3b with highest cytotoxicity. Anti-inflammatory assay of the compounds on RAW 267.7 cells revealed that the compounds N-(4-chlorophenyl)-2-[(trifluoroacetyl)amino]-1,3-thiazole-5-carboxamide (2a) and 2-amino-N-(4-chlorophenyl)-1,3-thiazole-5-carboxamide (3a) which are starting materials in the synthetic route of 7a significantly have similar nitrite reducing effect with indomethacin which is positive control compound. As regarding to analgesic activity, compound 3a showed the highest reducing activity on PGE(2) level induced by LPS than trifluoroacetylamino-substituted carboxamides 2a and 2b as compared with control group.
Keywords: Carboxamides; Imidazothiazole; Benzoxazole group; Cytotoxicity; Anti-inflammatory activity; Analgesic activity; ANTIMICROBIAL ACTIVITY; ANTITUMOR-ACTIVITY; ANTIBACTERIAL; BENZIMIDAZOLE; BENZOXAZOLONE; ANTICANCER; INHIBITORS; Chemistry